2017
DOI: 10.1021/acs.joc.7b02025
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxazine: A Privileged Scaffold for Radical-Trapping Antioxidants

Abstract: Diphenylamines are widely used to protect petroleum-derived products from autoxidation. Their efficacy as radical-trapping antioxidants (RTAs) relies on a balance of fast H-atom transfer kinetics and stability to one-electron oxidation by peroxidic species. Both H-atom transfer and one-electron oxidation are enhanced by substitution with electron-donating substituents, such as the S-atom in phenothiazines, another important class of RTA. Herein we report the results of our investigations of the RTA activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 61 publications
(163 reference statements)
4
67
0
Order By: Relevance
“…It occurs because the electronic delocalisation of the phenoxazine chromophore is increased in H 2 ‐xanthommatin, leading to greater stabilisation by resonance of the oxonium ion (O + ) (Schäfer & Geyer, ). Recent studies suggested that these redox and related antiradical behaviours allow phenoxazine‐based compounds to buffer oxidative stress (Romero & Martínez, ; Farmer et al, ; Shah, Margison & Pratt, ). The theoretical basis of this putative biological role was modelled using computational and quantum chemistry, as well as in biological assays.…”
Section: Ommochrome Biochemistry: From the Indole To The Phenoxazone mentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs because the electronic delocalisation of the phenoxazine chromophore is increased in H 2 ‐xanthommatin, leading to greater stabilisation by resonance of the oxonium ion (O + ) (Schäfer & Geyer, ). Recent studies suggested that these redox and related antiradical behaviours allow phenoxazine‐based compounds to buffer oxidative stress (Romero & Martínez, ; Farmer et al, ; Shah, Margison & Pratt, ). The theoretical basis of this putative biological role was modelled using computational and quantum chemistry, as well as in biological assays.…”
Section: Ommochrome Biochemistry: From the Indole To The Phenoxazone mentioning
confidence: 99%
“…Interestingly, this antiradical property was directly linked to the N–H bond of phenoxazine/phenothiazine rings (Fig. C) (Farmer et al, ), meaning that only reduced ommochromes could act as potent antiradicals and antioxidants in cells. This result is consistent with in silico measurements of hydrogen‐donor capacities of ommochromes (Fig.…”
Section: Ommochrome Biochemistry: From the Indole To The Phenoxazone mentioning
confidence: 99%
“…Additionally, the stability to one-electron oxidation is another determine factor for the potency of antioxidants (Farmer et al, 2017). Thus, we will elaborately discuss the types involved in reactivity to H-atom transfer and stability to one-electron oxidation of aminic RTAs in the following context.…”
Section: The General Radical-trapping Property Of Aminic Antioxidantsmentioning
confidence: 99%
“…If we draw the structure of DT‐PTZ‐C as the tautomer (Figure ), then it is apparent that further stabilization of the radical cation or the radical form is possible. In the case of molecules such as phenols and enolates, the most facile reaction available is the HAT (Jovanovic, Steenken, Boone, & Simic, ) and has also been invoked to explain the antioxidant activity of phenoxazines (Farmer et al., ). It is clear that defining the mechanism of action of DT‐PTZ‐C will require further research, which is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moosmann et al reported that three structurally similar compounds phenothiazine, phenoxazine, and iminostilbene had IC 50 's of 20-75 nM in their experimental paradigms. Separate studies on the radical trapping activity of unsubstituted N-10 phenoxazines demonstrated an ability to trap more two or more peroxyl radicals indicating the potential for this group of compounds (Farmer, Haidasz, Griesser, & Pratt, 2017;Lucarini et al, 1999).…”
Section: Novel Use For An Old Structurementioning
confidence: 99%